Selection of green peas for the canning industry with a small grain size - V. A. Ushakov; I. P. Kotlyar; I. M. Kaigorodova (Овощи России)
Relevance. Therefore, at present, varieties with an average seed size are used for the production of canned "green peas". In this regard, it is important to create varieties with a mass of 1000 seeds less than 150 g for the production of premium canned food.Methods. The object of research was the lines of hybrids of vegetable peas of different ripeness groups with a low weight of 1000 seeds.Results. At the initial stage of the work, plants with a low mass of 1000 seeds and green cotyledons were selected and brought to constant lines over several years. Over the years of sampling, the weather conditions were with sharp changes in temperature and precipitation. This made it possible to single out samples with low variability of the selected characters based on the totality of characters. In 2018-2019, the selected lines were studied according to the characteristics of productivity and manufacturability during the period of technical ripeness in the nursery of competitive variety testing of vegetable peas. To determine the duration of the technical ripeness period and its relationship with the yield, the green peas were harvested in three periods, starting with the minimum density indicators (34-35 units) and with an interval of three days. When determining the fractional composition of green peas, sample 4.12 was isolated, which received the varietal name Smaylik. Green peas of this variety had a fairly high uniformity and small grain diameter with a predominance of fractions of 5-8.5 mm and 8.6-9.9 mm. Sample 12.12 was close to Smaylik in its performance. According to the results of competitive variety testing, the Smaylik variety in 2019 was transferred to the State variety testing of the Russian Federation.